Continuous precipitable water vapor monitoring using GNSS - IGONDOVÁ, Miroslava; HEFTY, Ján (Contributions to Geophysics and Geodesy, 2008)
Permanent GNSS (Global Navigation Satellite Systems) observations are performed at hundreds of stations all over the world. If surface measurements of pressure and temperature are available the Precipitable Water Vapor (PWV) can be computed. It requires the values of ZTD (Zenith Total Delay) derived from continuous processing of GNSS observations and the dry component modeling using e.g. the Saastamoinen model. PWV time series from years 2002 to 2007 are computed and presented for GNSS stations GOPE and ZIMM. The annual seasonal effects within Central Europe have amplitude of about 7 mm and phase shift of 249 days. Comparison of PWV values derived from GNSS and radiosonde observations shows agreement with bias 1.2 mm and standard deviation 3.1 mm.